Efektivitas Air Rebusan Jahe Merah terhadap Intensitas Nyeri Haid - Eline Charla Sabatina Bingan (Politeknik Kesehatan Kemenkes Mamuju, 2021)
The menstrual cycle lasts an average of 28 days. During menstruation some young women will feel menstrual pain, or in medical language called dysmenorrhea which is caused by uterine muscle spasms. The purpose of this study was to determine the effectiveness of red ginger boiled water on menstrual pain in female students at the Health Polytechnic of Palangka Raya. This research method uses Pre-experimental research with One Group Control Pretest-Posttest Design study. The population of this research is female students at Poltekkes Palangka Raya and the sample size is 73 respondents with the sampling technique used is purposive sampling. The statistical test used in this study was the Wilcoxon test. The results of the statistical test showed the value of Z = -7.047, which means that giving red ginger drink 7.047 times can help reduce the intensity of pain during menstruation. Statistical test results obtained a p value of 0.001 (p <0.05) meaning that there is an effect of red ginger boiled water on decreasing the intensity of menstrual pain. There is an effect of red ginger boiled water on decreasing the intensity of menstrual pain.